Pembubaran Partai Politik Terhadap Sistem Demokrasi di Indonesia - Rifandy Ritonga (Law Faculty of Universitas Bandar Lampung, 2015)
The existence of political parties as a form of freedom of association is needed in a democracy. However, based on the existing practices and regulations, political parties turned out to be dissolved. The dissolution of political parties would be done bersadarkan laws and regulations specify the reason, the procedures and the legal consequences dissolution of a political party. The problem in this research is the process of dissolution of political parties in the colonial period up to the period of reform in Indonesia and the impact of dissolution of political parties in Indonesia against the democratic system in Indonesia. Dissolution of political parties each period is different, in the period before the reform dissolution of political parties is done without justice mechanisms are clear, unlike the case with the reform era to the present arrangements regarding the dissolution of political parties is increasingly clearly stipulated in the Constitution of the Republic of Indonesia Year 1945, in Article 24C of one of the authorities of the Constitutional Court is to decide the dissolution of political parties, more clearly set out in the judicial procedure in the dissolution of political parties of the Constitutional Court of the Republic of Indonesia Number. 12, 2008. The effect of dissolution of political parties against the democratic system in Indonesia did not have an impact on the democratic system applied in Indonesia. Due to the dissolution of political parties will only be done if a political party is contrary to the basic objectives and the constitutional order. Even more than in the dissolution of a political party which opposed the goal is to protect democracy itself, constitution, sovereignty, national security and the state ideology.